2016
DOI: 10.1007/s12311-016-0811-z
|View full text |Cite
|
Sign up to set email alerts
|

Interhemispheric Connectivity Characterizes Cortical Reorganization in Motor-Related Networks After Cerebellar Lesions

Abstract: Although cerebellar-cortical interactions have been studied extensively in animal models and humans using modern neuroimaging techniques, the effects of cerebellar stroke and focal lesions on cerebral cortical processing remain unknown. In the present study, we analyzed the large-scale functional connectivity at the cortical level by combining high-density electroencephalography (EEG) and source imaging techniques to evaluate and quantify the compensatory reorganization of brain networks after cerebellar damag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 131 publications
0
12
0
Order By: Relevance
“…Our investigation revealed MVF-related parietal-to-M1 coupling. Weakened parietal-to-M1 interactions (Grefkes and Fink, 2011, Takeuchi et al, 2012) have been previously identified in stroke, and restoring functional interactions among this network has been positively correlated with good recovery (Carter et al, 2010, van Meer et al, 2010, Wang et al, 2010, Grefkes and Fink, 2011, Rehme et al, 2011, Rehme et al, 2012, van Meer et al, 2012, De Vico Fallani et al, 2016). Mirror feedback, therefore, may be a useful clinical tool, as it has been shown to improve some outcomes in moderately to severely impaired patients (Thieme et al, 2012, Thieme et al, 2013, Pollock et al, 2014), and to activate specific networks that may favor recovery, particularly in patients who cannot otherwise engage their paretic hand in exercise.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Our investigation revealed MVF-related parietal-to-M1 coupling. Weakened parietal-to-M1 interactions (Grefkes and Fink, 2011, Takeuchi et al, 2012) have been previously identified in stroke, and restoring functional interactions among this network has been positively correlated with good recovery (Carter et al, 2010, van Meer et al, 2010, Wang et al, 2010, Grefkes and Fink, 2011, Rehme et al, 2011, Rehme et al, 2012, van Meer et al, 2012, De Vico Fallani et al, 2016). Mirror feedback, therefore, may be a useful clinical tool, as it has been shown to improve some outcomes in moderately to severely impaired patients (Thieme et al, 2012, Thieme et al, 2013, Pollock et al, 2014), and to activate specific networks that may favor recovery, particularly in patients who cannot otherwise engage their paretic hand in exercise.…”
Section: Discussionmentioning
confidence: 88%
“…Empirical evidence suggests that the activation of these regions (Grefkes and Fink, 2011, Rehme et al, 2011, Rehme et al, 2012), and restored interactions between these regions measured as functional and effective connectivity are important predictors of recovery (He et al, 2007, Carter et al, 2010, Wang et al, 2010, van Meer et al, 2012, De Vico Fallani et al, 2016). Therefore, understanding the MVF network interactions may unveil if mirror feedback has the potential to engage circuits in a manner that may be favorable for recovery.…”
Section: Introductionmentioning
confidence: 99%
“…This s-MMN paradigm was studied in subjects with unilateral cerebellar lesions to exploit the possibility of testing cortical responses with and without cerebellar processing in the same subject. Because of the well-known crossed organization of cerebro-cerebellar circuits, unilateral cerebellar damage will affect only the cerebral cortex of the contralateral hemisphere (Di Lazzaro et al, 1994a, b, 1995; De Vico Fallani et al, 2016).…”
Section: Cerebellum and Its Role In Predicting Perceptionmentioning
confidence: 99%
“…Only Zeng et al [14] and Caliandro et al [15] compared the features of the EEGs collected at the impaired zones with the those recorded at the healthy zones: Caliandro et al [15] observed no difference between the two hemispheres of the same subject, whereas Zeng et al [14] claimed that the method they proposed needed to be further validated on EEG time series. As regards high-density EEG studies, De Vico Fallani et al [18] applied source imaging to HD-EEG to evaluate the compensatory reorganization of brain networks after cerebellar damage during a finger extension task. Sixty-four-channel EEGs were acquired during alternating movement tasks.…”
Section: Introductionmentioning
confidence: 99%